2019
DOI: 10.14336/ad.2018.0926
|View full text |Cite
|
Sign up to set email alerts
|

Role of Regulatory T cells in Atorvastatin Induced Absorption of Chronic Subdural Hematoma in Rats

Abstract: Chronic subdural hematoma (CSDH) is a neurological disorder with a substantial recurrence rate. Atorvastatin is an effective drug for treating hyperlipidemia and known to improve neurological outcome after intracerebral hemorrhage. Previous studies have reported that atorvastatin treatment promotes hematoma absorption in CSDH, while the underlying mechanisms remain unclear. In this study, we investigated whether the anti-inflammatory effects of atorvastatin mediate absorption of CSDH. 144 male, Wistar rats (6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 38 publications
(39 reference statements)
0
29
0
2
Order By: Relevance
“…Lipid-lowering therapy has been shown to ameliorate asymptomatic intracranial atherosclerosis, which is a risk factor for vascular CI and dementia (Xie et al, 2018 ; Zou et al, 2018 ; Miao et al, 2019 ; Shetty et al, 2019 ). Atorvastatin treatment also improved cognitive outcomes and induced anti-inflammatory response in a rat model for a chronic subdural hematoma and intracerebral hemorrhage (Quan et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lipid-lowering therapy has been shown to ameliorate asymptomatic intracranial atherosclerosis, which is a risk factor for vascular CI and dementia (Xie et al, 2018 ; Zou et al, 2018 ; Miao et al, 2019 ; Shetty et al, 2019 ). Atorvastatin treatment also improved cognitive outcomes and induced anti-inflammatory response in a rat model for a chronic subdural hematoma and intracerebral hemorrhage (Quan et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…There was a negative correlation observed between triglycerides and MMSE scores. Hence lipid-lowering therapy can improve neurological outcome (Quan et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, more recent studies have focused on the immune response, with an emphasis on lymphocytic infiltration, as they contribute to brain recovery through hematoma resolution, neurogenesis, and axonal regeneration after ICH. Regulatory T cells were shown to mediate anti-inflammatory responses and improve neurological function in a chronic subdural hematoma rat model (Frost et al, 2019;Quan et al, 2019). These studies may provide emerging therapeutic targets for ICH .…”
Section: Mechanisms Of Bbb Dysfunction Secondary To Hemorrhagic Strokementioning
confidence: 91%
“…Clinical studies have indicated that atorvastatin, which is a 3hydroxy-3-methylglutaryl-coenzyme A reductase inhibitor, can effectively treat CSDH by promoting vessel maturation and inhibiting intracapsular inflammation (15)(16)(17). Furthermore, preliminary findings from a randomized proof-of-concept clinical trial have indicated that atorvastatin plus low-dose dexamethasone treatment was effective in reducing hematoma and neurological symptoms in patients with CSDH (14).…”
Section: Introductionmentioning
confidence: 99%